Assessing the diversity of smallholder rice farms production strategies in Sierra Leone. (1st March 2016) - Chenoune, R.; Belhouchette, H.; Paloma, S. Gomez y; Capillon, A.
Highlights: The best-performing farms all combine two ecosystems and cultivate both rice and oil palms. Introducing oil palm as a cash crop may intensify food production, but it could cause a risk of dietary imbalance. To discriminate rice household production strategies, the criteria of farm structure, means of production, as well as, production targets (market vs. self-consumption) should be always specified. The farmer challenge is to found a balance between the two ecosystems and between rice and oil palm. Summary: In Sierra Leone, several international organizations are trying to help the government improve the productivity of its rice farms, which currently have the lowest rice yields in West Africa. However, the various programmes attempting to increase rice production, and consequently rice self-sufficient food production, are handicapped by an absence of thorough studies explaining the way rice farmers take the available socio-economic, technical and natural production factors into account when making their decisions. The purpose of the current article is to assess rice production performance on smallholder rice farms in Sierra Leone. To achieve this goal, an agronomic and socio-economic survey was carried out among 180 rice farmers in the district of Bombali in Northern Sierra Leone. The survey, combined with a specific statistical analysis, made it possible to assess production strategies for rice farms according to various discriminant parameters (family size and composition, fallow duration, seeding density, labour availability, ecosystems, share of oil palm, distance from field to farm…). This analysis revealed that the rice smallholder farms that perform best are those growing rice under two ecosystems together with oil palm. Those farms have more income to purchase rice seed in years when production is low or if they have large families to feed. However, subsistence rice farms with one exclusive ecosystem will probably not be sustainable and they will not be able to satisfy their households' future rice needs.